Bachelor’s degree in German studies and then? the professional development of the 2008 BA German graduates from Universiti Putra Malaysia - Torsten, Schaar; Selke, Raimond; Ogasa, Nicole; Ang, Lay Hoon (Global Academy of Training and Research, 2015)
Objective: An ongoing tracer study project –January 2014 to October 2015 –aims to provide more comprehensive data on the professional development of BA German graduates from UPM.